Enhancing Malaysian graduates' employability skills : an application of modified quality function deployment - Mohamad Shukri Bin Abdul Hamid (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
Globalization has resulted in a highly competitive work environment and employers are looking for versatile graduates who are able to drive their organizations to compete successfully in the world market. Obtaining a good degree is no longer sufficient to get a job. Graduates must equip themselves not only with technical skills but, more importantly, with soft skills as well. The main objectives of this study are to identify the employability skills of Malaysian graduates; to assign priority to each skill; and to identify and evaluate the effectiveness of various approaches that endow the graduates with relevant employability skills. This research employs a modified version of the Quality Function Deployment (QFD) model, consisting of two methods, namely Extreme Pairwise Comparison with Median Rank (EPCMR) and Analytic Network Process (ANP). A total of 942 questionnaires were distributed among companies in Malaysia and 233 questionnaires were useable for the purposes of this study. In general, the gap analysis showed that employers perceive graduates‟ employability skills performance is lower than they desired. The highest gap between skill level and desired ability was found in communication skills, especially regarding English language usage. Using the Importance–Performance Analysis (IPA), 13 attributes were further analysed. The QFD application revealed that work integrated learning is the most effective approach in equipping graduates with employability skills. The implication of this study underscores the importance of universities striving to improve the employability skills of graduates by exposing them to more real world applications, such as practical training and hands-on learning. Universities need to continuously improve curriculum to suit the demands of the current job market.